Google Classroom - An Effective Tool for Online Teaching and Learning in this COVID era - Santosh Sheelavant (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Nationwide lockdown due to corona virus pandemic compelled the medical colleges toconduct online classes to compensate for the loss of academic period. Among all the available apps, Googleclassroom was found to be more user friendly app with many built in features. After using one month ofGoogle classroom app in the department of Forensic medicine, a feedback survey was done to know theeffectiveness of online classes and in particular about the advantages and disadvantages of Google classroomas a tool for teaching and learning online.Material and Methods: A Questionnaire which had both objective and open ended questions wasadministered to 150 phase II MBBS students who underwent online classes conducted by department ofForensic Medicine and 6 instructors who took classes.Results: Students felt that undergoing online classes was the best way of utilizing lockdown time (54%).Both students and teachers found the app very user-friendly and easy to navigate. Students felt that, usinganytime anywhere (68%), interaction through private comment section (90%), getting the constructivefeedback (86%) and material available for revision all the time (84%) were the advantages of Googleclassroom. While teachers found, tracking of assignment, grading system and record keeping as advantages.No automated update option, network issues, No search option and No integration were few disadvantagesquoted by students and teachers.Conclusion: Online classes are the best way of utilizing the lockdown time to make up the loss of academicperiod. Google classroom is an effective tool for teaching and learning online classes because of its ease ofuse and features which are both teacher friendly and student friendly